Effect of Wafer Off‐Angles on Defect Formation in Drift Layers Grown on Free‐Standing GaN Substrates. Issue 4 (27th November 2019) - Shiojima, Kenji; Horikiri, Fumimasa; Narita, Yoshinobu; Yoshida, Takehiro; Mishima, Tomoyoshi
Abstract : The effect of the surface off‐angle toward either the a ‐ or m ‐axis on the defect formation is characterized using deep‐level transient spectroscopy (DLTS) in conjunction with the carrier concentration for Ni Schottky contacts formed on n‐GaN drift layers. In both noncontact and conventional capacitance–voltage results, off‐angle dependence on carrier concentration is observed. For all samples, a large dominant peak appears at approximately 270 K in the DLTS spectra and is attributed to E3 ( E C  − 0.57–0.61 eV) defects. Carbon atoms can act as carrier compensators and form E3 defects. These results can be interpreted based on how C incorporation during crystal growth depends on the off‐angle. Abstract : The effect of the surface off‐angle toward either the a ‐ or m ‐axis on the defect formation is characterized using deep‐level transient spectroscopy for Ni Schottky contacts formed on n‐GaN drift layers. A large dominant peak appears at 270 K and is attributed to E3 defects. Carbon atoms can act as carrier compensators and form E3 defects.